Vibration harvesting process of olive trees based on response surface methodology and rigid-flexible coupling simulation - Dang, Kehua; Niu, Zijie; Mu, Haotian; Lan, Weike; Zhang, Xu; Xin, Di; Zhang, Jun; Cui, Yongjie (International Journal of Agricultural and Biological Engineering, 2025)
A trunk-vibrating screen is widely used in olive harvesting machinery. Because of the irregularity of fruit recovery efficiency, the recovery efficiency fluctuates greatly. Vibration harvesting parameters are important factors affecting the percentage of olive harvest. Therefore, the study of vibration picking parameters is of great significance for olive harvest. Vibration parameters, governed by tree morphological parameters, strongly influence the efficiency of vibration harvesting. In this study, a combination of response surface simulation and harvesting experiments was used to investigate the relationship between morphological and vibration harvesting parameters in “three open-center shape” olive trees. First, force analysis and experimental measurements were performed on the olive fruit, and the Box-Behnken design was used to obtain the vibration parameters through finite element simulation and to establish the response surface model of the parameters (main trunk diameter, main trunk height, main branch angles A and B) and the vibration parameters (vibration frequency and vibration force) of the “three open-center-shape” olive trees. In addition, the mapping relationship between tree shape parameters and vibration parameters was obtained. The results show that the 90% quantile of the acceleration of abscission of olives is 1113.35 m/s2; the average correlation coefficient between the simulation and the experiment results was 0.73, and the simulation was a good representation of the experimental results. When the tree shape was “three open-center”, the trunk diameter and height were related to the vibration harvesting parameters; the average harvesting efficiency of olives was 91.22%, and the resonance frequency of the monitoring points was similar to that of the simulation results. This study provides a reference for the design of vibration harvesting equipment and fruit tree shaping.Keywords: olive, three open-center shape, vibration harvesting, modal analysis, rigid-flexible coupling simulation, accelerationresponseDOI: 10.25165/j.ijabe.20251803.8792Citation: Dang K H, Niu Z J, Mu H T, Lan W K, Zhang X, Xin D, et al. Vibration harvesting process of olive trees based on response surface methodology and rigid-flexible coupling simulation. Int J Agric & Biol Eng, 2025; 18(3): 25–36.